2014
DOI: 10.1177/0884533614564995
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Management of the Post–Bariatric Surgery Patient

Abstract: Bariatric surgery is considered one of the most effective methods of achieving long-term weight loss when all other medical treatments have failed. The number of bariatric procedures increases each year. Nevertheless, bariatric procedures are associated with a number of complications that require careful multidisciplinary management. Nutrition supervision is of substantial value, as malnutrition, vitamin, and micro- and macronutrient deficiencies may lead to deleterious consequences. In this review, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 69 publications
1
43
0
14
Order By: Relevance
“…The absorption kinetics of lipids and proteins are largely unknown. Exclusion of major parts of the stomach and changed admixture of food with gastropancreatic enzymes have been suggested to impair or delay protein digestion (9). Therefore, we investigated the effect of RYGB on the appearance of amino acids in the systemic circulation from orally ingested protein as well as from endogenous sources during a mixed meal.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption kinetics of lipids and proteins are largely unknown. Exclusion of major parts of the stomach and changed admixture of food with gastropancreatic enzymes have been suggested to impair or delay protein digestion (9). Therefore, we investigated the effect of RYGB on the appearance of amino acids in the systemic circulation from orally ingested protein as well as from endogenous sources during a mixed meal.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss is achieved by restrictive and malabsorptive processes 7. Postoperatively, patients who have undergone Roux-en-Y gastric bypass are at risk of a number of vitamin and mineral deficiencies 8. In order to minimise these deficiencies, recommended nutrient supplementation regimens are employed and vary depending on the specific operative procedures undertaken 9…”
Section: Discussionmentioning
confidence: 99%
“…25 Both the early and late intervention classes were more likely to intervene if the cause of obesity was perceived to be from lifestyle rather than genetic factors. [28][29][30][31][32][33] There is growing evidence that genetics may play a greater role in obesity than once believed; increasing education may be required to overcome this bias. 26,34 Our study also demonstrated that both classes were more likely to intervene if no surgery was involved, and hesitancy increased as surgical interventions became more invasive.…”
Section: Discussionmentioning
confidence: 99%
“…30,36 It is possible that participants are less likely to intervene if surgery is involved because they are assuming that multidisciplinary care, which is integral to success in a bariatric surgery program, is already being provided. [31][32][33][34] The follow-up period in tertiary healthcare centers of patients receiving surgical treatment is typically fairly short; therefore, it is important for clinicians to continue to provide long-term follow-up and care for their patients. 31,32 Clinicians in both the late and early intervention classes were also more likely to refer or treat obese patients if a multidisciplinary team and consultation service were available at their facility.…”
Section: Discussionmentioning
confidence: 99%